1999
DOI: 10.1002/(sici)1521-3951(199909)215:1<531::aid-pssb531>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Critical Doping in Overdoped High-Tc Superconductors: a Quantum Critical Point?

Abstract: Evidence is presented from the scaling of the Knight shift, entropy and transport properties together with the sharp peaking of condensation energy, critical currents, superfluid density and a variety of other physical properties for the occurrence of a common critical doping point in lightly overdoped high-T c superconductors (HTS). This critical doping lies at the point where the doping-dependent normal-state pseudogap energy, E g , falls to zero and bears a strong, though incomplete, resemblance to a quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
97
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 27 publications
16
97
0
Order By: Relevance
“…Moreover, in our results, the peak of the Hall number is found to be at p∼0.15, to the left of the optimal doping point (p=0.16). For a doping level of p∼0.15 the value expected for T * , the pseudogap crossover temperature, roughly matches 180 K [30]. Quantum oscillation experiments [18,[31][32][33] showed that while there is a large hole-like Fermi surface in the overdoped regime, there are only small pockets in the underdoped regime.…”
Section: Indications Of An Electronic Phase Transition In Two-mentioning
confidence: 67%
“…Moreover, in our results, the peak of the Hall number is found to be at p∼0.15, to the left of the optimal doping point (p=0.16). For a doping level of p∼0.15 the value expected for T * , the pseudogap crossover temperature, roughly matches 180 K [30]. Quantum oscillation experiments [18,[31][32][33] showed that while there is a large hole-like Fermi surface in the overdoped regime, there are only small pockets in the underdoped regime.…”
Section: Indications Of An Electronic Phase Transition In Two-mentioning
confidence: 67%
“…The parallels with several families of materials where the superconducting dome has been discovered in the vicinity of purely electronic ordered phase, dressing the quantum critical point [16][17][18] strengthen the viewpoint of excitonic superconductivity in 1T-TiSe 2 . On the other hand, the continuous development of the soft phonon mode in the vicinity of the CDW transition, both in Cu-intercalated and pure and pressurized material [8,34,35], suggests that the lattice deformation may not be regarded as a secondary effect that simply follows the electronic ordering.…”
Section: Fig 1 (Color Online)mentioning
confidence: 83%
“…The dependence of the superconducting transition temperature on the copper content shows a domelike structure, characteristically found in phase diagrams of cuprate high-temperature superconductors, some heavy fermion compounds and layered organics [15][16][17]. The superconductivity in those compounds is thought to be tightly related to neighboring antiferromagnetic ordering, with superconductivity appearing around a (purely electronic) quantum critical point (QCP) [16,18]. On the other hand the case of 1T-TiSe 2 signals the possibility of a novel state, where superconductivity emerges around a new type of quantum critical point, unrelated to magnetic degrees of freedom [4,8].…”
mentioning
confidence: 98%
“…The normal state of the underdoped and optimally doped SC region also shows unusual non-Fermiliquid (FL) behaviors. There are increasing evidence for a Quantum Critical Point (QCP) around the optimal doping which is responsible for the unusual properties of the SC and the normal phase [7,8,9,10]. For the electrondoped (n-type) cuprates, on the other hand, antiferromagnetism survives until the superconductivity appears over a narrow range of x around the optimal x ∼ 0.15.…”
mentioning
confidence: 99%